ANALISA PEMBOROSAN BAHAN BAKAR MINYAK AKIBAT KEMACETAN PADA RUAS JALAN DI KOTA MATARAM (STUDI KASUS JALAN DR. WAHIDIN REMBIGA KOTA MATARAM) - I NENGAH AGUS PURNATA; MADE MAHENDRA; I DEWA MADE ALIT KARYAWAN (Universitas Mahasaraswati K. Mataram, 2023)
The increase in the population of Mataram City resulted in an increase in traffic volume, due to the increase in the use of private vehicles for various community activities. This is the cause of traffic problems, especially congestion on several road sections, one of which is the Rembiga Road Section. Congestion causes losses to road users, judging from the use of vehicle fuel oil. In connection with this problem, research was conducted with the aim of finding out how much waste of fuel oil caused by congestion. Analysis of vehicle fuel oil consumption using PdT-15-2005-B Highways guidelines and analysis of vehicle fuel oil waste by determining the difference in the value of fuel oil consumption, congestion current conditions and free flow conditions. From the results of the analysis, it was found that the value of fuel oil waste on Monday 341 lt / km / day with fuel costs of Rp. 3,242,056.00 / km / day, Saturday 240 lt / km / day (Rp. 2,294,864.00 / km / day) and Sunday 135 lt / km / day (Rp. 1,296,993.00 / km / day). On Monday there is a high waste of fuel oil due to rush hour heavy traffic volume and high level of side obstacles, so travel time increases due to low vehicle speed.